2021
DOI: 10.1158/2159-8290.cd-20-1219
|View full text |Cite
|
Sign up to set email alerts
|

A Role for SMARCB1 in Synovial Sarcomagenesis Reveals That SS18–SSX Induces Canonical BAF Destruction

Abstract: Reduced protein levels of SMARCB1 (a.k.a. BAF47, INI1, SNF5) have long been observed in synovial sarcoma (SS). Here, we show that combined Smarcb1 genetic loss with SS18-SSX expression in mice synergized to produce aggressive tumors with histomorphology, transcriptomes, and genome-wide BAF-family complex distributions distinct from SS18-SSX alone, indicating a defining role for SMARCB1 in SS. Smarcb1 silencing alone in mesenchyme modeled epithelioid sarcomagenesis. In mouse and human SS cells, SMARCB1 was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 47 publications
6
53
0
Order By: Relevance
“…We confirmed similar results at the gene expression level by in-silico analysis using mRNA-seq and clinicopathological data from the TARGET-OS project. Our findings are consistent with previous works that support the anti-tumorigenic role of SMARCB1 [ 14 , 27 , 30 ]. To our knowledge, this study is the first to show SMARCB1 expression as a potential prognostic biomarker and indicator of advanced disease status in osteosarcoma.…”
Section: Discussionsupporting
confidence: 94%
“…We confirmed similar results at the gene expression level by in-silico analysis using mRNA-seq and clinicopathological data from the TARGET-OS project. Our findings are consistent with previous works that support the anti-tumorigenic role of SMARCB1 [ 14 , 27 , 30 ]. To our knowledge, this study is the first to show SMARCB1 expression as a potential prognostic biomarker and indicator of advanced disease status in osteosarcoma.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, other studies suggest that SS18-SSX alters BAF genome distribution and subtype levels and therefore increases the complex’s ability to disrupt PRC2 function. This disruption could mediate activation of gene expression through the COMPASS family of histone H3K4 methylases and orchestrate aberrant oncogenic transcriptional programs 13 , 38 , 39 . A study from Banito et al found that SS18-SSX fusions associate with KDM2B-PRC1.1, a noncanonical polycomb repressive complex 1, to aberrantly activate transcription factors that are targets of polycomb-mediated gene repression 40 .…”
Section: Discussionmentioning
confidence: 99%
“…SS18-SSX may induce degradation of the canonical BAF-complex (cBAF). Since we observed significantly higher expression of the polybromo-associated BAF (pBAF) specific components ARID2 , SMARCE1 and PHF10 in SSC-I, it is implied that SSC-I is dominated by the pBAF complex [50, 51]. SCNAs were similar to vascularized SS (SSC-II) and evidently less frequent than in epithelial-SS (SSC-III), indicating that the hyperproliferative phenotype arises de novo and is not a progression from SSC-II/III.…”
Section: Discussionmentioning
confidence: 99%